Prevalence and factors associated with safe male circumcision among Makerere University undergraduate students, Kampala - Uganda - Nyamwiza, Jean; Mukisa, John; Ictho, Jerry; Ssenyonga, Ronald; Nalutaaya, Annet; Kawooya, Ismael; Benjamin, Temper; Nagendo, Joanita; Musewa, Angella; Ali, Sam; Lako Ernesto Loro, Emmanuel; Agaba, Bekiita Bosco; et al. (Research Square, 2019)
Background Safe male circumcision (SMC) is currently recognized as a preventive strategy in reducing the risk of HIV; however, the prevalence of circumcised men in Uganda is still quite low at 26%. This study aimed to determine the prevalence and factors associated with SMC and among Makerere University undergraduate students, in Kampala Uganda. Methods We conducted a cross-sectional study among 602 participants selected using multistage probability sampling strategy. Pretested semi-structured questionnaires and focus group discussions were used to collect data. Quantitative data were analyzed with Stata 12.0, the prevalence ratio and p-values were calculated. Possible interactions and confounding variables were assessed with the Poisson regression model while qualitative data was analyzed with content analysis. Results The overall prevalence of safe male circumcision among male undergraduates was 58.3% (95% CI: 54.37 – 62.24). Factors associated with SMC prevalence included: safety of SMC procedure (Prevalence Ratio (PR) = 1.13, 95% Confidence Interval (CI): 1.03 – 1.25) and friendly health workers (PR = 0.78, 95% CI: 0.74 – 0.83). The perceived benefits of SMC included hygiene (86.5%, n = 521), reduced risk of HIV transmission (4.5%, n = 26) and reduced risk of penile cancer (45.7%, n = 275) while, the perceived barrier was pain (10.1%, n = 61). The students perceived that SMC recipient’s first sexual partner post-procedure should not be his girlfriend. Most participants in all the focus group discussions perceived SMC increases sexual pleasure. Conclusion The overall self-reported SMC success rate among participants was high, along with the safety of SMC services and friendly health workers as important factors among male students. There is a need for continuous sensitization campaigns and communication strategies to address beliefs about SMC, some related misconceptions, and barriers so as to increase its prevalence.
Keywords: Safe male circumcision; Makerere University undergraduate students; Uganda